The effects of fartlek and continuous training methods and training motivation on improving physical fitness among senior high school students - Muhammad Aziz Daraktuni; Arsil Arsil; Syahrastani Syahrastani; Sefri Hardiansyah (Journal of Educational and Learning Studies, 2026)
Objective: This study aimed to examine the effects of Fartlek and continuous training and training motivation on physical fitness among senior high-school students. Methods: A quasi-experimental 2 × 2 factorial design involved 40 students assigned according to training model and high or low motivation. Physical fitness was assessed using the Indonesian Student Fitness Test (TKSI), and data were analyzed using two-way ANOVA and Tukey tests. Results: Continuous training produced higher fitness scores than Fartlek training (F = 8.11), while motivation significantly affected fitness (F = 7.62). A significant interaction between training model and motivation was identified (F = 7.33). The highest fitness score occurred in the continuous-training/high-motivation group (M = 23.00). Conclusion: Continuous training was more effective, particularly among highly motivated students, confirming that training effectiveness depends on motivational characteristics